The Influence of Social Media Marketing, Electronic Word of Mouth, And Live Streaming on Impulse Buying on Tiktok Shop - Ni Komang Alit Prameswari Atmaja; I Gusti Ngurah Agung Gede Eka Teja Kusuma; Made Pradnyan Permana Usadi (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Online shopping behavior is continuously increasing as community lifestyles increasingly follow year-to-year trends. The strong desire for individuals to look attractives is one of the causes for the high usage of marketplace sites for online shopping. The purpose of this study is to determine the influence of socials media marketings, electronics words of mouth, and live streaming on impulse buying. The sample in this study consists of 112 respondentss who are TikTok Shop consumers in Denpasar City. Research sampling was conducted using the purposive sampling method. The data analysis technique used is regressions analysis. The research results state that socials media marketings has a positives and significants effects on impulse buying, electronics words of mouth has a positives and significants effects on impulse buying, and live streaming does not influence impulse buying.